Comparing the collective behavior of banking industry in emerging markets versus mature ones by random matrix approach - Vahabi, H.; Namaki, A.; Raei, R. (Frontiers in Physics, 2022)
One of the essential features of capital markets as an adaptive complex network is their collective behavior. In this paper, we have analyzed the collective behavior of banking sectors of four stock markets, which are composed of emerging and mature ones. By plotting the dendrograms and heat maps of the correlation matrices, it is found that the mature markets are more similar to each other. By applying the method of Random matrix theory(RMT), one of the important complexity notions, and its tools: participation ratio(PR) and relative participation ratio(RPR), it is obvious that mature markets have a lower degree of collective behavior than the emerging ones. By perturbing the correlation matrix of these markets, it is found that the mature markets are more vulnerable. It means that emerging markets that have lower cross-correlations are less vulnerable to perturbations. The findings of this paper are useful for policymakers of these countries to concentrate on the market structures and their behaviors.